PTU-055 Interim data and experience in the ibd anaemia service evaluation project – a new role for the ibd registry. (17th June 2017) - Silva, A Castro; Waddingham, W; Oliver, D; Knight, P; Johnson, M; Bloom, S; Magwenzi, S; Munro, C; Cummings, F
Abstract : Introduction: Iron deficiency anaemia (IDA) is a common complication of Crohn's disease (CD) and Ulcerative Colitis (UC), with estimated prevalence between 36%–76%. Both IDA and its treatment can be associated with significant disease morbidity, particularly fatigue. This 12 month pilot investigation, preceding a wider UK audit, aims to utilise the IBD Registry Web Tool to capture the prevalence of IDA in an outpatient setting and the consistency and quality of treatment patients receive, which are currently uncertain. Method: In a Joint Working project between the IBD Registry and Pharmacosmos, patients were recruited at 5 hospitals: UCLH, Southampton, UHSM, James Cook, and Luton and Dunstable. At each site, 20 consecutive patients were recruited until 10 patients with CD and 10 with UC were enrolled, giving a total of 100 patients for the study. Patients gave permission for their data including demographics, disease activity scores, IBD Control Questionnaire, and blood parameters relating to IDA to be used by the Anaemia Service Evaluation and IBD Registry. Results: We report baseline data for patients at enrolment. Average age was 44 years 11mos (19–90 years). Mean HBI score was 3.7 based on 57 recorded scores and UCDAI was 2.4 from 13 patients. Using the Physician's Global Assessment, 3.7% had severe, 13.4% moderate, 26.8% mildly active and 56.1% quiescent disease. 18 patients were anaemic; 9 men and 9 women, with mean Hb114.4±13.7 g/L and 110.9±4.2 g/L respectively. 9 additional patients were iron deficient without anaemia. In anaemic patients, mean ferritin and CRP were 100.3 µg/L and 12.1 mg/L respectively. Ferritin and CRP were 69.9 µg/L and 7.7 mg/L in non-anaemic patients. Mean patient-reported IBD control-8 scores (range 0–16) were 11.47 (anaemic) and 11.45 (non-anaemic). 52 patients reported fatigue while 26 missed activities due to their disease. Conclusion: In this pilot study, once patients were consented and entered on the IBD Registry Web Tool, adding blood results and disease scores was straightforward. This could easily be done in an outpatient clinic setting once the clinician is familiar with the process. This initial data set confirms the feasibility of effectively monitoring anaemia with the IBD Registry to enhance detection of under-recognised symptoms such as fatigue and help improve patient care. Our initial experience suggests that the IBD Registry serves as a reliable and meaningful way of capturing quality improvement data regarding IDA and its treatment in IBD. Disclosure of Interest: None Declared